Iron status, movement disorders, and acute phase response in elderly psychiatric patients. Issue 2 (February 1994) - Treloar, A J; Crook, M A; Tutt, P; White, D P; Philpot, M P
Abstract : The previously reported relation between iron deficiency and movement disorders was studied in a population with a high prevalence of both problems. There was no evidence of a direct statistical relation between iron deficiency and movement disorders. Significant associations were, however, found between movement disorders and features of the acute phase response to physiological stress. Indices of iron status are known to be affected by the acute phase response and it is suggested that the previously reported abnormalities in iron status may be secondary to this.